Brief communication: The potential use of low-cost acoustic sensors to detect rainfall for short-term urban flood warnings - N. Peleg; H. Torelló-Sentelles; G. Mariéthoz; L. Benoit; J. P. Leitão; F. Marra; F. Marra (Natural Hazards and Earth System Sciences, 2023)
Floods in urban areas are one of the most common natural hazards. Due to climate change enhancing extreme rainfall and cities becoming larger and denser, the frequency, magnitude, and impact of these events are expected to increase. Pluvial floods can occur in urban areas within minutes. A fast and reliable rainfall detection system should thus be implemented in flood-prone cities to warn the public of upcoming floods and save lives and reduce damage. The purpose of this brief communication is to discuss the potential implementation of low-cost acoustic rainfall sensors in short-term flood warning systems.